The Effects of Evaluative Sequencing on Performance, Behavior, and Attitudes. - Rosen, L.S.; Howe, Keith R.; Baldwin, Bruce A. (The Accounting Review, 1983)
ABSTRACT: This paper is an extension of prior research by Paretta and Chadwick [1975] that investigated the effect of question sequencing on examination performance. In this work, the investigation is broadened to trace the effects across all examinations in a course, as well as to examine effects on student attitudes and dropout behavior. A sample of elementary financial accounting students (n=414) was administered examinations throughout the semester that differed in the order of question difficulty. One-third took examinations with questions ordered easiest to hardest, one-third took examinations with random sequencing of questions, and one-third took examinations ordered hardest to easiest. Comparative examination scores, dropout statistics, and end-of-semester course evaluations were analyzed. No evidence was found to support the contention that question sequencing affected examination performance or dropout behavior from the class. Significant differences were observed, however, in student attitudes toward the course, instructor, and field of accounting.